Mechanism of Phellodendron and Anemarrhena Drug Pair on the Treatment of Liver Cancer Based on Network Pharmacology and Bioinformatics - Ruan, Xiaofeng; Li, Wenyuan; Du, Peng; Wang, Yao (Frontiers in Oncology, 2022)
ABSTRACT Background: This study aims to explore the key targets and signaling pathways of The traditional Chinese medicine Phellodendron and Anemarrhena drug pair for the treatment of liver cancer. Methods: Firstly, bioinformatics technology was used to analyze GSE62232 gene chip to obtain the differential genes of liver cancer. A network pharmacology technology was used to find the active components of PADP and their targets. Secondly, the differential genes were imported into String database to draw a PPI network, and network topology structure map combined with Cytoscape software. In addition, the R language was used to identify differential gene targets and pathways through GO and KEGG pathway enrichment analysis. Finally, AutoDock Vina were used for molecular docking of core targets and core compounds. Moreover, GEPIA online analysis tool was used to perform survival analysis of the core target genes. RT-PCR was used to verify the changes of target genes. Results Firstly, a total of 21,654 genes were obtained. After screening, 1019 differential genes were obtained, including 614 down-regulated genes and 405 up-regulated genes. Furthermore, after screening by ADME standards, 52 active ingredients were obtained, of which 37 were Phellodendron and 15 were Anemarrhena. And a total of 36 differential genes have been identified, including 13 up-regulated genes and 23 down-regulated genes. Secondly, through enrichment analysis and verification of RT-PCR, it was found that PADP could up-regulate the genes such as CCNB1, CDK1, NQO1, AKR1C3, and CCNA2, and down-regulate ERS1, AR, FOS, CYP1A1, CYP3A4, CYP1A2, CYP2B6, ABCG2, HMOX1, CCL2 and other genes. It might through the p53 signaling pathway, IL-17 signaling pathway, TNF signaling pathway and Toll-like receptor signaling pathway, thereby regulating the cell cycle, inhibiting cell proliferation, metastasis, apoptosis and senescence. Finally, the molecular docking results showed that there was certain affinity between the core compounds and core target genes. Moreover, ESR1, AR, CCNB1, CDK1, AKR1C3 and CCNA2 may become potential target genes for the survival and prognosis of PADP for the treatment of liver cancer. Conclusion PADP may treat liver cancer through multiple targets, multiple channels, and multiple pathways, thereby suppressing cancer cells and improving the living quality of patients.